Thermal conductivity of graphene polymorphs and compounds: From C3N to graphdiyne lattices. (May 2020) - Hatam-Lee, S. Milad; Rajabpour, Ali; Volz, Sebastian
Abstract: Tremendous experimental and theoretical attempts to find carbon based two-dimensional semiconductors have yielded a wide variety of graphene polymorphs, such as carbon-nitride, carbon-boride, graphyne and graphdiyne 2D materials with highly attractive physical and chemical properties. In this study, by conducting extensive non-equilibrium molecular dynamics simulations, we have calculated and compared the thermal conductivity of fifteen prominent carbon-based structures at different lengths and two main chirality directions. Acquired results show that the structures of C3 N, C3 B and C2 N exhibit the highest thermal conductivity, respectively, which suggest them as suitable candidates for thermal management systems in order to enhance the heat dissipation rates. In contrast, generally graphdiyne lattices and in particular 18-6-Gdy graphdiyne yield the lowest thermal conductivity, which can be a promising feature for thermoelectric applications. As a remarkable finding, we could establish connections between the thermal conductivity and density or Young's modulus of carbon based 2D systems, which can be employed to estimate the thermal conductivity of other polymorphs. Those results can provide a comprehensive viewpoint on the thermal transport properties of the nonporous and exceedingly porous carbon based 2D materials and may be used as useful guides for future designs in thermal management. Graphical abstract: Image 1